Analisis Kesiapan Peserta Didik SMA Negeri 8 Padang Menghadapi Revolusi Industri 4.0. - Yogica, Relsas; Fuadiyah, Sa?diatul; Hasanah, Jihan (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
Industrial Revolution 4.0. is a time when human life is very dependent on the information base. This forces everyone to be ready, and have global competitiveness. The trick is to be able to adapt to technological developments, be able to use it, and be able to sort out the appropriate functions of technology, so that their use is effective. All aspects of life are affected, including formal education in high school. Here, the teacher plays an important role. Carry out learning with the orientation towards proficient technology, and wisely use technology. However, the implementation of the learning certainly requires basic thinking, how much ability students have. There are no data that reveal the readiness of students in secondary schools to face the Industrial Revolution 4.0, including in SMA Negeri 8 Padang. Thus, we conducted this descriptive study. We used a questionnaire, JRZ-IR4.0, to collect data from 603 students. Then, the data is analyzed and concludes the students' readiness. The results showed that the level of student readiness was quite ready, with an average of 3.18 and 3.15 points. These results form the basis for considering the direction of the learning process.